2020
DOI: 10.3390/ijerph17196941
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Biochemical Effects of Stress in Pregnancy

Abstract: Prenatal stress has been linked to preterm birth via inflammatory dysregulation. We conducted a cross-sectional study on female participants who delivered live, singleton infants at University of Pittsburgh Medical Center Magee Women’s Hospital. Participants (n = 200) were stratified by cumulative risk scores using a combination of individual factors (maternal education, diabetes, hypertension, smoking, relationship status, obesity, depression) and neighborhood deprivation scores. We hypothesized that inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…A systematic review of adverse birth outcomes demonstrated a robust relationship between low-SES and either preterm birth or low birth weight in 92 of 106 studies reviewed. 9 Similarly, our findings are congruent with national 29 We suspect that the inconsistent findings of prior studies may result from two attributes of pregnancy inflammation. First, inflammatory factors operate in a coordinated fashion, and the cumulative activity of multiple biomarkers may be more important than the levels of one or two isolated cytokines.…”
Section: Discussionsupporting
confidence: 85%
“…A systematic review of adverse birth outcomes demonstrated a robust relationship between low-SES and either preterm birth or low birth weight in 92 of 106 studies reviewed. 9 Similarly, our findings are congruent with national 29 We suspect that the inconsistent findings of prior studies may result from two attributes of pregnancy inflammation. First, inflammatory factors operate in a coordinated fashion, and the cumulative activity of multiple biomarkers may be more important than the levels of one or two isolated cytokines.…”
Section: Discussionsupporting
confidence: 85%
“…1 In contrast, a growing body of knowledge, particularly generated and disseminated by Black women scholars, continues to illuminate the association between perinatal health inequities and historical and contemporary racism. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Unfortunately, translating this knowledge into meaningful change is challenging. A growing body of work highlights the failure of leading scholars and journals, 1,17,18 funders, 7 and large-scale quality improvement organizations 19,20 to earnestly interrogate racism as a critical driver of health inequities.…”
Section: Introductionmentioning
confidence: 99%
“…Racial disparities in maternal health outcomes in the United States are not the result of inherent biological differences but are a direct outcome of racism experienced by women of color. Racism and social disadvantage are intertwined structural determinants of health in the United States, with Black mothers more likely to receive repetitive prenatal stress from systemic discrimination [ 12 ]. State-level indicators of structural racism in employment and education were found to be directly associated with differences in infant mortality rates for Black but not White women in the United States [ 13 ].…”
Section: Introductionmentioning
confidence: 99%